METHODS OF USING VIRTUAL EDUCATIONAL TECHNOLOGIES IN TEACHING PRIMARY PREPARATORY SCIENCE (Academia Science Repository, 2023)
In this article, a method of using virtual educational technologies was created in the teaching of the science of primary preparation until the general convocation, and the improvement of the methodology of introducing virtual educational technologies was widely explained.